2022
DOI: 10.3389/fpsyg.2021.753758
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Frequency Reduction in Human Groups Performing a Joint Oscillatory Task

Abstract: In human groups performing oscillatory tasks, it has been observed that the frequency of participants' oscillations reduces when compared to that acquired in solo. This experimental observation is not captured by the standard Kuramoto oscillators, often employed to model human synchronization. In this work, we aim at capturing this observed phenomenon by proposing three alternative modifications of the standard Kuramoto model that are based on three different biologically-relevant hypotheses underlying group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Future work may compare the delay-coupled model presented here with other numerical solutions ( cf. Roman et al, 2019 ; Shahal et al, 2020 ; Calabrese et al, 2022 ), as well as with analytical solutions such as linear delay differential equations ( cf. Yi and Ulsoy, 2006 ) and networks of delay-coupled oscillators ( Pérez et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future work may compare the delay-coupled model presented here with other numerical solutions ( cf. Roman et al, 2019 ; Shahal et al, 2020 ; Calabrese et al, 2022 ), as well as with analytical solutions such as linear delay differential equations ( cf. Yi and Ulsoy, 2006 ) and networks of delay-coupled oscillators ( Pérez et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lombardi et al 18 also showed that the behaviour of a human in such tasks can be learnt, even to the extent that they captured the individual motor signature of the particular human being modelled. The dynamics of such patterns have also been modelled for groups of more than two humans 20 23 .…”
Section: Introductionmentioning
confidence: 99%